AdOPTION AND ADAPTATION OF IMPROVED SOIL MANAGEMENT PRACTICES IN THE EASTERN UGANDAN HILLS. (26th September 2011) - Mcdonagh, J.; Lu, Y.; Semalulu, O.; Fleskens, Luuk; Stringer, Lindsay C.
Abstract This research investigated empirically the qualities of improved soil management practices (ISMPs) most likely to lead to land user adoption. Land users' perceptions of soil‐related constraints were investigated in two hillside districts of eastern Uganda. The research looked at land user rationale for adopting and adapting specific ISMPs at the end of a two‐year period of increased advice and support. Land user engagement with soil management improved markedly after this period of support and multifunctionality, that is, provision of a number of different products or benefits, was seen to be a common characteristic of those ISMPs taken up by land users. It is argued that in the search for 'best‐bet' ISMPs, multifunctionality may be a particularly relevant and easily measurable indicator of likely adoption of a practice by land users. The research also demonstrates the value of supporting land users in their efforts to adapt ISMPs to fit with their own circumstances. Copyright © 2011 John Wiley & Sons, Ltd.